The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/dddt.s232325
|View full text |Cite
|
Sign up to set email alerts
|

<p>Potential Use of Microbial Surfactant in Microemulsion Drug Delivery System: A Systematic Review</p>

Abstract: Background: Microemulsions drug delivery systems (MDDS) have been known to increase the bioavailability of hydrophobic drugs. The main challenge of the MDDS is the development of an effective and safe system for drug carriage and delivery. Biosurfactants are preferred surface-active molecules because of their lower toxicity and safe characteristics when compared to synthetic surfactants. Glycolipid and lipopeptide are the most common biosurfactants that were tested for MDDS. The main goal of the present system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 49 publications
(83 reference statements)
0
28
0
Order By: Relevance
“…28,29 Compared to a conventional emulsion, a microemulsion is a better vector for the active agents because it consists of nanodroplets that allow better penetration of these active agents. [30][31][32] It also has the advantage of being prepared cold, [33][34][35] which on the one hand reduces energy consumption during its preparation, and on the other hand, it uses heat-sensitive active ingredients. Thus, in comparison with micellar solutions, microemulsions can solubilize a greater quantity of active agents due to their greater stability partly due to the presence of a greater quantity of surfactant, which can, on the other hand, constitute an obstacle to their use for reasons of cost and/or toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Compared to a conventional emulsion, a microemulsion is a better vector for the active agents because it consists of nanodroplets that allow better penetration of these active agents. [30][31][32] It also has the advantage of being prepared cold, [33][34][35] which on the one hand reduces energy consumption during its preparation, and on the other hand, it uses heat-sensitive active ingredients. Thus, in comparison with micellar solutions, microemulsions can solubilize a greater quantity of active agents due to their greater stability partly due to the presence of a greater quantity of surfactant, which can, on the other hand, constitute an obstacle to their use for reasons of cost and/or toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it was also suggested that surfactin can effectively demulsify waste crude oil (Yang et al, 2020 ). Their emulsifying property also confers them a potential of application in the food and cosmetics area for the product formulation (Mnif et al, 2013 ; Varvaresou and Iakovou, 2015 ; Zouari et al, 2016 ) as well as in the pharmaceutical area for the formulation of stable microemulsion drug delivery systems (Ohadi et al, 2020 ).…”
Section: Structure and Properties Relationshipmentioning
confidence: 99%
“…In the biomedical industry, protein–surfactant systems are used for the production of hydrogels (Afinjuomo et al 2019 ; Castelli et al 2008 ). The hydrogels form the base of fibrous proteins such as fibroin, which are used for tissue regeneration and drug delivery (Park et al 2014 ; Dubey et al 2018 ; Ohadi et al 2020 ).…”
Section: Surfactant–protein Interactionsmentioning
confidence: 99%